Gastroprotective activity of the paste of Evolvuius alsinoides L. (vishnukranti kalka) in rats - Hewageegana, H.G.S.P.; Ariyawansa, H.A.S.; Ratnasooriya, W.D. (My University, 2006)
This study examined the gastroprotective activity of vishnukranti kalka (paste) which is recommended in Ayurveda for the treatment of peptic ulcers. The kalka was made by mixing the dry powder of the whole plant of Evolvuius alsinoides L with cow ghee, bee honey and common sugar (1:2:2:1 w/w). The gastroprotective activity was tested usmg the rat alcohol induced gastric lesion model following oral administration of either the kalka (1250 mg/kg, 2500 mg/kg, 5000 mg/kg), placebo- 1 (5000 mg/kg of wheat floiu", cow ghee, bee honey and common sugar), placebo-2 (5000 mg/kg of cow ghee, bee honey and common sugar), cimetidine (100 mg/kg) and distilled water. The results showed a strong and dose depended gastroprotective activity of vishnukranti kalka (in terms of length and number of raacroscopical mucosal haemoniiagic lesions). Placebo-1 and placebo-2 also had gastroprotective activity but was less potent to kalka. Vishnukranti kalka significantly increased the pH of gastric juice and its mucus and carbohydrate contents. The kalka was well tolerated even with chronic administration with no renaltoxicity (in terms of urea and cratinine), hepatotoxicity (in terms of SGOT and SGPT) and haematotoxiciry (in terms of packed cell volume, red blood cell coimt, white blood cell count, and haemoglobin concentrations). It is concluded that vishnukranti kalka has strong and safe oral gastroprotective activity and the study also provides scientific evidence for thejustificationofitsuseasagastroprotectiveagentinAyurvedicmedicine. ,